2003
DOI: 10.1086/376526
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cavitary and Fibrosing Pulmonary and Pleural Aspergillosis: Case Series, Proposed Nomenclature Change, and Review

Abstract: We describe 18 nonimmunocompromised patients with chronic pulmonary aspergillosis. Duration of the disease ranged from several months to >12 years. All 18 patients had prior pulmonary disease. Weight loss, chronic cough (often with hemoptysis and shortness of breath), fatigue, and chest pain were the most common symptoms. All 18 patients had cavities, usually multiple and in 1 or both upper lobes of the lung, that expanded over time, with or without intraluminal fungal balls. All had detectable Aspergillus pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
578
4
48

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 486 publications
(663 citation statements)
references
References 42 publications
(49 reference statements)
19
578
4
48
Order By: Relevance
“…A. fumigatus was the most frequently isolated Aspergillus species (n = 14), followed by A. niger (n = 5), A. flavus (n = 2), and A. terreus (n = 1) in all CPA cases; while A. niger was the predominant isolated species in CNPA cases (n = 4). Anti- progressed to form well-defined cavit es; and 2) the cavities were pre-existing (i.e., in cases of previous tuberculosis or bronchiectasis) [4]. However, the former radiographic features are concordant with those of Binder's CNPA or Gefter's SIA.…”
Section: Laboratory Findings Of Patients With Cpamentioning
confidence: 97%
See 1 more Smart Citation
“…A. fumigatus was the most frequently isolated Aspergillus species (n = 14), followed by A. niger (n = 5), A. flavus (n = 2), and A. terreus (n = 1) in all CPA cases; while A. niger was the predominant isolated species in CNPA cases (n = 4). Anti- progressed to form well-defined cavit es; and 2) the cavities were pre-existing (i.e., in cases of previous tuberculosis or bronchiectasis) [4]. However, the former radiographic features are concordant with those of Binder's CNPA or Gefter's SIA.…”
Section: Laboratory Findings Of Patients With Cpamentioning
confidence: 97%
“…infection. In the last decade, new clinical nomenclature and definition of chronic forms of aspergillosis have been proposed [3][4][5], and recent guidelines from the Infectious Diseases Society of America (IDSA) have indicated 3 major subtypes of chronic forms of pulmonary aspergillosis, namely CNPA (categorized in subacute invasive form of aspergillosis; subacute IPA), chronic cavitary pulmonary aspergillosis (CCPA), and aspergilloma [6]. Aspergilloma was traditionally classified as simple or complex in the surgical literature, and complex aspergilloma is considered CCPA by current IDSA guidelines [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…6 Proposed enrollment criteria for prospective clinical studies of CPA by Denning with minor modifications were used for this trial. 5 Patients with CPA had to fulfill the following conditions: (1) the existence of at least one of the symptoms in the complex consisting of fever, weight loss, sputum, cough, hemoptysis, fatigue, and shortness of breath; (2) new infiltrates, cavity formation, or expansion of pre-existing cavities with or without peri-cavitary infiltrates and adjacent pleural thickening; (3) at least one positive result of serologic tests including the Platelia Aspergillus test (Fujirebio, Tokyo, Japan) for detecting Aspergillus galactomannan antigen by enzyme-linked immunosorbent assay (cut-off value, 1.0), the Aspergillus immunodiffusion system (Microgen Bioproducts, Ltd., Camberley, United Kingdom) for anti-Aspergillus antibody detection, and the (1,3)--D-glucan test (cut-off value, 11.0 pg/ml; Wako Pure Chemical Industries, Osaka, Japan ; and cut-off value, 20 pg/ml for the Fungitec G Test, Seikagaku Corporation, Tokyo, Japan) and/or any positive evidence of the existence of Aspergillus spp. by molecular diagnosis, culture, or pathological findings; (4) positive findings of at least one of the inflammation markers such as white blood cell (WBC) counts, value of C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR); (5) lack of improvement of symptoms or signs after at least 3 days administration of broad-spectrum antibiotics.…”
Section: Patientsmentioning
confidence: 99%
“…1,2 Several names of these chronic forms of disease have been proposed: semi-invasive aspergillosis 3 , chronic necrotizing pulmonary aspergillosis (CNPA) 4 , simple or complex aspergilloma, and chronic cavitary and fibrosing pulmonary aspergillosis (CCPA and CFPA). 5 As Hope et al 6 indicated apparently distinct entities do not exist for this syndrome and these forms usually overlap. The common characteristics of these forms, however, consist of 1) underlying pulmonary disorders, 2) the status of low-grade immunosuppression, and 3) less than severe findings of angioinvasion in histopathology.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation